Discovery of highly potent dual EP2 and EP3 agonists with subtype selectivity. Issue 3 (1st February 2016) - Kinoshita, Akihiro; Higashino, Masato; Aratani, Yoshiyuki; Kakuuchi, Akito; Matsuya, Hidekazu; Ohmoto, Kazuyuki
Graphical abstract: Abstract: The cyclic carbamate derivatives, 2-[2-((4 S )-4-(1E, 3 R )-8-fluoro-3-hydroxy-4, 4-dimethyl-1-octenyl-2-oxo-1, 3-oxazolidin-3-yl)ethyl]sulfanyl-1, 3-thiazole-4-carboxylic acid (5 ) and 2-[2-((4 S )-4-(1E, 3 R )-3-[1-(4-fluorobutyl)cyclobutyl]-3-hydroxy-1-propenyl-2-oxo-1, 3-oxazolidin-3-yl)ethyl]sulfanyl-1, 3-thiazole-4-carboxylic acid (7 ) were identified as the first potent dual EP2 and EP3 agonists with selectivity against the EP1 and EP4 subtypes. Compounds5 and7 demonstrated highly potent dual EP2 and EP3 agonist activity with EC50 values of 10 nM or less. In addition, these compounds possess structural features distinct from natural prostaglandins, such as a cyclic carbamate moiety, a dimethyl or cyclobutyl group and a terminal fluorine atom.